ANALISIS AKSES TERHADAP KUALITAS PELAYANAN KESEHATAN BAGI MASYARAKAT MISKIN DALAM PERSPEKTIF PEMBIAYAAN KESEHATAN ERA JKN DI INDONESIA - Tasya Salsabila; Saumy Ramadini, Desi Amanda Sari, Fitriani Pramita Gurning (CV. Adiba Aisha Amira, 2024)
Being healthy is essential for performing daily tasks. The Indonesian government has introduced several health-related public policies in an effort to improve health conditions. The aim of this research is to determine the relationship between the quality of health services and health insurance in Indonesia. The method used is to analyze articles published in the last 5 years through Google Scholar, Sinta, and Garuda searches. The results of this research are that limited access to health services is closely related to the poor health status of poor people. Due to financial (economic) and geographical limitations. The main challenges experienced by underprivileged communities in accessing health services are lack of funds, remote location of health facilities, and transportation constraints. Good health is supported by adequate and superior facilities. Health advances are critical to fighting poverty. Improving the quality, affordability and equity of basic health services; expanding the number and caliber of health workers; ensuring the safety and efficacy of food and medicines; providing health services during regional disasters; increasing health promotion and community empowerment; and increasing access to health, especially for the poor, is the goal of the health services sector. The insurance industry needs to provide services that provide protection for humans, especially those related to activities that are beneficial to public health.